The influence of pharmaceutical care in patients with advanced non-small-cell lung cancer receiving combination cytotoxic chemotherapy and PD-1/PD-L1 inhibitors - Kou, Wen; Lin, Yan Yan; Su, Fei; Xiang, Yue; Qiao, Hui; Wu, Xin’An; Hou, Xiao-Ming (Frontiers in Pharmacology, 2022)
Background: Immune checkpoint inhibitors combined chemotherapy (ICIC) are widely used for various types of lung cancer in the past decade. However, ICIC related adverse events (AEs) are more serious than immune-related adverse events (irAE) or cytotoxic chemotherapy alone. Objective: This prospective interventional study aimed to evaluate the impact of the pharmaceutical care program in reducing adverse events and analyze pharmacy interventions in patients with NSCLC who receive ICIC therapies. Method: NSCLC patients were enrolled in this study, the pharmaceutical care program was introduced after patients received the second cycle ICIC therapies, and were followed by the pharmacist for 6 months after hospital discharge. The percentages of adverse events between patients in and after the first two cycles were analyzed and compared. Results: After the first two treatment cycles, the clinical pharmacist proposed 67 interventions in 30 patients. The most frequent types of intervention were drug discontinuation (40.3%, 27/67) followed by drug modification (14.9%, 10/67). There were significant decreases in AEs after the second cycle with respect to nausea (≥grade-2, 14% vs. 28.3%, p = 0.039), constipation (≥grade-2, 8.8% vs. 21.7%, p = 0.039), diarrhea (≥grade-2, 6% vs. 16.7%, p = 0.031), and myelosuppression (≥grade-2, 15.8% vs. 30.0%, p = 0.022). Conclusion: Provision of pharmaceutical care for NSCLC patients receiving ICIC therapies can optimize drug therapy and reduce adverse events.